The Influence of Enterprise Risk Management and Corporate Social Responsibility on Firm Value with Profitability as a Moderation Variable - Febrian Hardi; I Gde Kajeng Baskara (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Improving shareholder wealth is a primary goal for a company which can be achieved by increasing the firm value. Maximizing profit can enhance the firm value, but it is not sufficient to ensure the long-term sustainability of the company. Firm value can be influenced by financial aspects such as profitability and non-financial aspects such as Enterprise Risk Management (ERM) and Corporate Social Responsibility (CSR). This research aims to analyze the influence of ERM and CSR on firm value with profitability as a moderating variable in technology sector companies listed on the Indonesia Stock Exchange. The population of technology sector companies is 22 companies. The sample was selected using a purposive sampling method, the results were 19 companies. Data was collected from company annual reports from 2020-2023. Data analysis was carried out using Moderated Regression Analysis techniques. The research results show that ERM and CSR have no significant effect on firm value and profitability is unable to moderate the influence of ERM and CSR on firm value.